Management algorithms and artificial intelligence systems for cardiopulmonary bypass. (November 2022) - Condello, Ignazio; Santarpino, Giuseppe; Nasso, Giuseppe; Moscarelli, Marco; Fiore, Flavio; Speziale, Giuseppe
This article introduces management algorithms to support operators in choosing the best strategy for metabolic management during cardiopulmonary bypass using artificial intelligence systems. We developed algorithms for the identification of the optimal way for assessing metabolic parameters. Different management algorithms for extracorporeal procedures interfaced with metabolic monitoring systems already exist on the market and are applied in clinical practice. These algorithms could provide guidance for selecting the best metabolic strategy with the aim at reducing human error and optimizing management.